Foot‐and‐mouth disease outbreaks in captive scimitar‐horned oryx (Oryx dammah). Issue 4 (14th February 2020) - Lignereux, Louis; Chaber, Anne‐Lise; Saegerman, Claude; Heath, Livio; Knowles, Nick J.; Wadsworth, Jemma; Mioulet, Valérie; King, Donald P.
Abstract: This paper describes three episodes of foot‐and‐mouth disease (FMD) that were detected during 2013–2015 in scimitar‐horned oryx ( Oryx dammah ) (SHO), a large Sahelo‐Saharan antelope extinct in the wild housed in a wild ungulate breeding facility located 50 km east of Abu Dhabi, United Arab Emirates. While no mortality attributable to FMD was noted in the population of nearly 4, 000 SHO during two of the three outbreaks, the morbidity varied according to the circulating strains and seroconversion reached a plateau of 78.0% within two weeks and remained at this level for at least nine months. Partial or complete sequencing of the VP1 encoding region demonstrated that the three outbreaks were caused by three different FMDV lineages (O/ME‐SA/PanAsia‐2, A/ASIA/Iran‐05 and O/ME‐SA/Ind‐2001), consistent with FMD viruses that are circulating elsewhere in the region. These findings demonstrate that SHO are susceptible to FMD and highlight the risks of virus incursion into zoos and captive facilities in the Arabian Peninsula.